Schistosomiasis: Snail-vector control, molecular modelling and dynamic studies of bioactive N-acetylglycoside saponins from Tetrapleura tetraptera. (December 2018) - Taiwo, Bamigboye J.; Olubiyi, Olujide O.; Wang, Xue; Fisusi, Funmilola A.; Akinniyi, Ganiyu Akintayo; Van Heerden, Fanie R.; Strodel, Birgit
Graphical abstract: Highlights: NADH-ubiquinone oxidoreductase and RXR are two therapeutic targets in B. glabrata . Molecular docking predicted binary complexes with T. tetraptera N- acetyl saponins. Molecular dynamics studies displayed varying saponins strength with binding pocket. N- acetyl saponin can be lead compound for drug development in snail-vector control. Abstract: Schistosomiasis, a chronic neglected tropical disease caused by the Schistosoma spp. parasite, is associated with disabling patient symptoms. The new focus of the WHO roadmap on 'transmission control, wherever possible' offers drug development opportunities for intermediate-host control to prevent human-to-snail-to-human parasite transmission. Reports on the analysis of the impact of 'chemical-based mollusciciding' have concluded that constant application of molluscicides may contribute significantly towards the elimination of schistosomiasis in endemic areas. In South-Western Nigeria, Tetrapleura tetraptera is a tree whose fruit has been widely used in snail vector control. The presence of molluscicidal N -acetyl triterpene glycosides in the fruit has been reported. In this study, a bioactivity-directed fractionation of the fruit extract was performed to isolate the most potent molluscicidal saponin from the fruit. In an attempt to provide mechanistic insight into the observed activity, in silico screening was performed, profiling the molluscicidal N -acetyl triterpene glycosides reported from the fruit against two potential therapeutic targets in the mollusk used, NADH-ubiquinone oxidoreductase (NAD1) and retinoid X receptor. The docking predicted binary complexes of the saponins, which were subjected to explicit solvent conformational sampling from which patterns of structural stability were obtained. The binding energies alone did not account for the potency of the saponins indicating the influence of other factor like pharmacokinetic parameters. The study concluded that there is a preferential suitability of ND1's MWFE site for the rational design and development of novel molluscicidal agents.